On cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from South India and Sri Lanka, with descriptions of new taxa - Anisyutkin, Leonid N. (Zootaxa, 2014)
The new genus Indoapterolampra, gen. nov. and two new species (I. rugosiuscula sp. nov. and Morphna lucida sp. nov.) are described. Rhabdoblatta praecipua (Walker, 1868) is removed from the synonymy with ’Polyzosteria’ terranea Walker, 1868. The latter species is considered Epilamprinae gen. sp. The lectotype of Phoraspis (Thorax) porcellana Saussure, 1862 is designated. A key for the genera of Epilamprinae from South India and Sri Lanka is provided. Detailed morphological descriptions of the studied taxa are given. The structure of the male genitalia of I. rugosiuscula sp. nov., M. lucida sp. nov., M. plana (Brunner von Wattenwyl, 1865), M. decolyi (Bolivar, 1897) and R. praecipua and that of the female genital complex of M. decolyi, P. (T.) porcellana and Phlebonotus anomalus (Saussure, 1863) are described for the first time. Some aspects of the cockroach evolution are briefly discussed.